The Effect of Standardized Guidelines of Intra-Aortic Balloon Pump Care on Length of Stay in Cardiac Patients - Yasmeen Ghafoor, Hajra Sarwar, M. Afzal, Asif Hanif, Amir Gilani, Samreena Ghafoor (Pakistan Journal of Medical & Health Sciences, 2022)
Length of stay in the Intensive care units is special as an outcome. The adverse outcome is defined as the length of stay ≥ 5 days that is 120 hours and the normal length of stay was defined as < 5 days. Standardized guideline developed for nurses practice to reduce the length of stay in cardiac patients durnning the of intra-aortic balloon pump support. This guidelinewas very helpful for nurse’s practices to reduce the length of stay. heart transplantation is the gold standard management for cardiac patients with advanced congestive heart failure and myocardial infraction. Mechanical circulatory support devices have been gradually used as a ‘bridge’ in order to stand organ function and stabilizehemodynamics while patients remain on the transplant waiting list or undergo left ventricular assist device surgery. The intra-aortic balloon pump (IABP) is a myocardial assist device that was first introduced into clinical practice in 1968.The procedure of counter pulsation wasfirstlydesignated by Dr Adrian Kantrowitz in 1953. Aim of study: To assess the effect of standardized guidelines of intra-aortic balloon pump care on the length of stay in cardiac patients. Study Design: Randomized control trial Sample: Randomly, 72 nurses were included in the current study. Setting: The research was conducted in cardiac intensive care units of the Punjab Institute of cardiology Lahore.